Entrepreneurship Course’s Effects on Islamic State University of North Sumatera’s Management Students’ Entrepreneurship Spirit - Wildan Izzaty; Zuhrinal M. Nawawi (International Journal Labs, 2022)
The biggest challenge that must be faced for a country is to reduce unemployment in the country. Various efforts are made by the government to reduce unemployment, efforts in the form of community empowerment, providing more knowledge of entrepreneurship, and instilling an entrepreneurial spirit in each individual. The purpose of this study is to find out how influential entrepreneurial subjects have on students' entrepreneurial interest in management majors. The research method conducted in the form of a purposive sampling method with a data collection tool is a questionnaire distributed to 80 respondents. The results can be found in this study that the entrepreneurship courses taught in the 7th semester in the management study program are very influential on the interest of students to become an entrepreneur judging from intrinsic factors and extrinsic factors.